Dissemination of Web-Based Data Weigher Survey Application as A Quantitative Research Aid Facilitator - Stephanus Ivan Goenawan; Kumala Indriati; Agustinus Silalahi; Rory Anthony Hutagalung (Journal of Innovation and Community Engagement, 2024)
The knowledge dissemination of the data weighing survey application was motivated by the need for professionals, lecturers, or researchers, to retrieve respondents' data online as well as to process quantitative data directly. This survey application is in the form of a web-based questionnaire system using the Order Average Data Weigher Analysis (DWA) method which can collect and process large amounts of data or Big Questionnaire Data (BQD). The questionnaire system was made not to focus on one area or goal but can be used by all parties from any part. The method of implementing this knowledge dissemination is in the form of training, both theory and practice, directly creating and filling out online questionnaires. The purpose and benefits of this questionnaire system for professionals, lecturers, or researchers are to facilitate quantitative questionnaire research easily. This can happen because in the questionnaire application with the DWA system, there is an effective and efficient method for processing large amounts of questionnaire data automatically which is directly connected to G-Sheets on a web-based questionnaire system. The result and impact of this knowledge dissemination is that the participants benefit in the form of new knowledge of data scales and applications that can be directly used in assisting quantitative questionnaire-based research.